Experimental analysis of transverse jet using various decomposition techniques - Bayraktar, Seyfettin; Yilmaz, Tamer (KOREAN SOC MECHANICAL ENGINEERS, 2011)
This experimental study reports on testing of a single circular jet in crossflow (JICF) for three different jet-to-crossflow velocity ratios: R=0.5, 1.0, and 1.5. Velocity measurements were made using a hot-wire anemometer. Experimentally obtained JICF data were processed using Fourier, wavelet, and proper orthogonal decomposition (POD) techniques. Power spectrum obtained by Fourier analysis shows that flow at the center of nozzle has better laminar property than subsequent stations. The principle observation is that when jet exit velocity increases, the energy of the flow decreases. The center of the nozzle jet acts as an obstacle and damps the effect of the crossflow. Wavelet analysis reveals the dominant frequencies of the flow to 45 Hz for R=0.5 and 85-105 Hz for R=1.0. Energy distribution of the flow was also calculated by using the POD technique; results show that lower velocity ratio carries more energy of the flow.
Keywords: Constant temperature anemometer; Experiments; Fourier analysis; Hot-wire anemometer; Proper orthogonal decomposition (POD); Turbulence; Wavelet; Wind tunnel; CROSS-FLOW; BOUNDARY-LAYER; SIMULATION; EVOLUTION; HOLES; Engineering